Unforgetting as a choreographic practice - Styve Holte, Solveig (Peripeti, 2024)
Unforgetting as choreographic practice questions how artistic research can contribute to the remembering of dance histories and a re-contextualisation through performance. Opening the creation process of the performance Frå Form til Famling (2023), Holte shares experiences from the encounter with these dance historical archives, transforming a document into an artistic experience to create a space for a polyphonic remembering, an unforgetting that expands the initial narrative, and that creates a space for remembering several histories at once.